Mathematical Representation Ability of Middle School Students through Model Eliciting Activities with STAD Type - Zairisma, Zairisma; Apriliani, Vina; Yunus, Johan (Universitas Islam Negeri Raden Intan Lampung, 2020)
The ability of mathematical representation is one of the abilities that must be possessed by students in learning mathematics. In fact, students 'mathematical representation ability is still relatively low, so we need a learning model that can improve students' mathematical representation abilities, namely Model Eliciting Activities (MEA) with STAD type. The purpose of this study is to compare the mathematical representation ability of students taught using MEA with STAD type and those taught with conventional learning. The approach to be used is a quantitative approach with a quasi-experimental research method and using a control group pretest-posttest design. The population in this study were all VII grade students. Sampling was done using simple random sampling, which consisted of two classes, class VII1 as the experimental class and class VII2 as the control class. Data collection is used by using a mathematical representation ability test sheet. The data analysis technique used is independent t-test. Based on these analysis it can be concluded that the mathematical representation ability of students taught using MEA with STAD type is better than conventional learning.